AVA DATABASE CONNECTIVITY (JDBC) - DATA ACCESS TECHNOLOGY (International Journal of Engineering and Computer Science, 2013)
A serious problem facing many organizations today is the need to use information from multiple data sources that have been developed separately. To solve this problem, Java Database Connectivity came into existence. JDBC helps us to connect to a database and execute SQL statements against a database. JDBC API provides set of interfaces and there are different implementations respective to different databases. This paper emphasis on its history and implementation, architecture and JDBC drivers.